Archives damage atlas : a tool for assessing damage - van der Most, Peter (Metamorfoze The HagueNL, 2010)
Aims to assist with recognition of and to classify damage to archival documents in order to establish the level of accessibility. Also helps to provide more insight in the types and causes of damage.